Characterisation of stress corrodes specimens - Azmie Mohd Ariffin
This final year project is about to investigate the morphology on the failure surface of the specimens after stress corrosion test. It will also reveal different morphology for immersed and unimmersed specimens using Specimen Electron Microscopic, SEM.